(3cJGH aj GdJGQjNs
(3ChdgG (B:s
(3hai fUa ThGd gPG hUd GdYdGeI GdUGHhfi HGSJOYGA GdSdWGf dg ef HdO GdNdjd Ydjg GdSdGe s
(3BNQgG (B:s
(3ai GdYTQ GdCNjQ ef QeVGf hGUd GdGMHGQ eQGcT s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hjHJOi ef SfI (B883 (3hjfJgi YfO cQg SfI (B904 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs